Analysis of segments of helicopters’ works market as an element of strategic planning of helicopter construction company - Yu. V. Krivolutsky (Путеводитель предпринимателя, 2021)
Current studies, connected to research of state and condition of use of helicopters, do not give a clear picture of market demand for types and modification of helicopters. Hence, there is no strait answer how the helicopters construction company should react to the market demand uncertainty. The need for deeper research in the shown direction grows constantly. The marketing results will enable helicopter construction company to segment the works of the helicopters and based on that to define its development strategic goals.